Óptima repuesta a la demanda para estaciones de carga de vehículos eléctricos con alta incertidumbre considerando el perfil de voltaje en la red de distribución. - Benalcázar López, Byron Daniel (2017)
This document shows an analysis of the behavior of the voltage profile in the distribution network by the insertion of charge of different Electric Vehicles (EVs) in different periods of time and amount of load, it is analyzed the voltage profiles since they are an indicator of The reliability of an electrical system. Based on several recharge scenarios, it is possible to determine the percentage of affectation to the current distribution network and whether the network can supply the load of the EVs. By means of a heuristic based on the Hungarian algorithm it is possible to estimate the behavior of the demand of the distribution networks and the variation of the voltage profiles, and it is possible to discriminate the optimum hours for the recharge of the batteries of the EVs. The analysis is associated with the prediction of the maximum power that a four-bay charging station can have at different times, considering slow, fast and super fast load, each of them with different level of affectation to the network, also looking for the Correct load management of EVs to increase the efficiency, quality and reliability of distribution networks.